A Study of Soluble Proteins(Spl and Sp2) Effect of extracted from Proteus mirabilis on the Activity of Superoxide Dismutase,SOD in the Sera of albino rabbit - Al-Abd el waheed, L.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The  a i m  of  the  present  study  is  to  shed  some  light  on  theimm u nol ogica l     effect   of  so lub l e  protei ns  extracted   from  Proteu mirabilis  th rough  em ployi ng t he  level  of  the en zy mati c  activity  of Superoxide Dismutase,SOD.The    olublc  proteinsÂ·Sp I       and  Sp2,were  extracted   by  usi ng th e lysosyme   enzyme  .The  rabbits  were divided  into three groups  ,the fir t one was injected with Spl, the second with Sp2 for four weeks a nd the th ird one was the  control group.The   results   reveal ed   tha t    enzymatic   activ i ty   of   Superox ideDismutase,SOD   was  sign ificantly  increased  in  the  fi ft h  weekes  of injection with S p I        com pa red with contro l   group.Th e sam e effects of the Sp2   were obser  ed in specific enzymatic activ i ty of Su peroxide Dismutase,SOO.Therfore,the extracted  soluble proteins had an effect on the innate immune respon e of the rabbits.